Correlation of Knowledge Level with Prevention Practice of Tuberculosis Transmission among Household Contacts in Sungai Kunjang Sub-District, Samarinda City - Ayu Andini Saleha; Joko Pramono; Tini (International Journal of Scientific Multidisciplinary Research, 2023)
Household contacts of Tuberculosis (TB) sufferers are significantly at risk of contracting TB because of the proximity and intensity of interaction. TB transmission can be avoided with preventive practices among household contacts.   This study aims to analyze the correlation of knowledge level with TB transmission prevention in household contacts of TB sufferers in Sungai Kunjang District, Samarinda City. This study used an analytical survey design with a cross-sectional approach. The sample of this study, as many as 67 respondents, was taken purposively on household contacts of TB patients. The results of the chi-square test analysis obtained a p-value = 0.239 (> α =  0.05). This study concludes that there is no relationship between knowledge variables and variables of TB transmission prevention practices among household contacts of TB sufferers. It is recommended that health workers provide health education with TB transmission prevention practices